Association of Hyperprolactinemia with Female Infertility: A Prospective Study of 200 Patients - Fiza Jamil, Uzma Asif, Saba Ayoub, Tanzila Sarfraz, Qamoos Razzaq (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hyperprolactinemia is a prevalent disorder associated with infertility in women. It disrupts the hypothalamic-pituitary-gonadal axis, leading to anovulation and menstrual disturbances. Early identification and appropriate treatment of hyperprolactinemia can restore fertility in many affected women. Objective: This study aims to determine the prevalence of hyperprolactinemia in infertile women, examine its association with infertility, and assess the efficacy of treatment. Methods: This prospective study involved 200 women, aged 20-40 years, who presented to the outpatient department with infertility. Serum prolactin levels were measured, and elevated levels were treated with dopamine agonists. We performed logistic regression analysis to explore the relationship between hyperprolactinemia and infertility. Results: The prevalence of hyperprolactinemia was 31%, and 80% of women who received dopamine agonist therapy achieved pregnancy. Logistic regression analysis confirmed a significant association between elevated prolactin levels and infertility (OR: 2.6, 95% CI: 1.7-3.8). Conclusion: Hyperprolactinemia is a significant factor in female infertility. Early diagnosis and appropriate treatment can enhance fertility outcomes. Keywords: Hyperprolactinemia, Female Infertility, Dopamine Agonists, Ovulation Induction, Prolactin, Logistic Regression.